MARKETING STRATEGY FOR THE HOUSEHOLD CASSAVA CHIPS INDUSTRY IN KALOSI VILLAGE, ALLA DISTRICT, ENREKANG DISTRICT - Darmiati Dahar; Muh. Jabal Nur (PIRSAP (Paser Institute for Scientific Research and Publications), 2024)
The development of regional superior-based agro-industrial areas is regional development that creates a healthy climate, adds value to raw materials and creates employment opportunities. Agroindustry development will spur economic growth. The agro-industrial commodity is cassava. Cassava is not durable and has a low price, if managed well it can provide high added value. Cassava (Manihot esculenta) is an important source of carbohydrates. The food industry meets food needs and generates foreign exchange for the country.